PENGARUH KARAKTER EKSEKUTIF DAN CORPORATE GOVERNANCE TERHADAP TAX AVOIDANCE DI INDONESIA (Studi pada Perusahaan Manufaktur yang terdaftar di BEI periode tahun 2012-2014) - Sani Hardiyanti Ashari (AKT 16 UMY 081, 2016)
The purpose of this research is to examine the effect of executive characteristic and corporate governance toward tax avoidance in Indonesia at manufacture companies that listed in Bursa Efek Indonesia (BEI). Population in this research is manufacture companies that listed in BEI in period of 2012 through 2014. Sample is determined with purposive sampling method, for 45 companies. This research data is obtained from Indonesian Capital Market Directory (ICMD) and www.idx.co.id. Multiple linear regression method is used as data analyze method in this research. The result shows that executive characteristic variable have a negative and not significant effect toward tax avoidance in Indonesia. Meanwhile, corporate governance variable has a positive and significant effect toward tax avoidance in Indonesia. Keywords : executive characteristic, institutional ownership, the proportion of commissioners, audit committee, quality audit, corporate governance, tax avoidance